Understanding school ineffectiveness: A study in five Mexican schools with low academic performance - Duarte Cruz, José María; Valenti Nigrini, Giovanna (IE Revista de Investigación Educativa de la REDIECH, 2022)
This article analyzes some attitudes, interactions, and practices associated with goals, values, motivations, and expectations of principals, teachers, parents and mothers of families from five public primary schools identified as having low school effectiveness. Initially, a statistical analysis of the ENLACE 2012 and PLANEA 2015 and 2016 tests was carried out, which identified schools with high and low school effectiveness. Through qualitative case studies, it was explored how managerial management and leadership, teacher and family involvement influence the effectiveness of these schools. Some findings indicate trends in ineffective schools towards authoritarian management, there are communication, leadership and organization problems; there is little teacher commitment, low expectations of educational achievement, traditional pedagogies are used and focused on the reproduction of content. There is little family involvement, family-school relationships are fractured, hierarchical and distant, which in general promotes a school climate with tensions, sometimes conflict and low educational achievement.